(untitled) (Modern information system and technologies, 2018)
In the article reviewed the methods Development of the accounting system of activities restaurant type. The purpose of the work is to develop a document management system for a company with a limited scope of functions, which will allow the user to conduct daily operations efficiently and conveniently. Development methods include studying the material, using object-oriented programming, working with databases MySQL.